Analisis Bibliometrik Tren Penelitian Mahasiswa di Politeknik Kesehatan Kementerian Kesehatan Surabaya - Zuraida, Shinta Sisca; Hidayah, Imas Rahmadhtul; Sya'diyah, Aimmatus (Perpustakaan Universitas Gadjah Mada, 2025)
This study aims to determine the trends in student thesis research at the Surabaya Ministry of Health Polytechnic from 2020 to 2024. This study employs the bibliometrics method (co-occurrence analysis of co-word calculations). Bibliometric analysis is used to identify the most frequently occurring keywords and analyse their frequency of occurrence to determine the dominant research topics in student theses at Poltekkes Kemenkes Surabaya. Data visualisation was performed using the VOSviewer application to illustrate the relationships between keywords that frequently appeared together in a single study. Based on the results of the VOSviewer software analysis, the research trends of students at the Surabaya Ministry of Health Polytechnic from 2020 to 2024 are as follows: 1) The Health Analyst Department has research trends on Candida Albicans, Staphylococcus Aureus, Haemoglobin, Escherichia Coli and Diabetes Mellitus; 2) The Nutrition Department has research trends on nutritional status; 3) The Midwifery Department has research trends on postpartum care, midwifery care, and knowledge; 4) The Nursing Department has research trends on knowledge, hypertension, nursing care, COVID-19, and the elderly; 5) The Dental Nursing Department has research trends on Knowledge, Dental Caries, Pregnant Women, and Dental and Oral Hygiene; 6) The Environmental Health Department has research trends on Behaviour, Body, and Physical Conditions of Houses; and 7) The Electromedical Technology Department has research trends on BPM, Calibration, Temperature, Arduino, and SPO2.